"One Size Does Not Fit All": Revisiting Team Feedback Theories From a Cultural Dimensions Perspective. Issue 2 (April 2020) - Gabelica, Catherine; Popov, Vitaliy
Feedback is a critical component of teamwork regulation. Research underscores the importance of feedback processes for its effectiveness in teams and further notes how individual differences can affect these processes. Nonetheless, few have theorized on the cultural dimensions associated with feedback to specify how these can attenuate such processes. We contend that research can be advanced by specifying how cultural dimensions may shape individual perception and processing of feedback and team processing of feedback in homogeneous and heterogeneous teams with respect to cultural dimensions. To address this foundational question, we review and integrate the literature on feedback in teams and culture in teams by (a) incorporating the role of culture in team feedback models, (b) discussing how cultural dimensions could influence the perception and processing of feedback, and (c) highlighting important directions for future inquiries at the intersection of feedback and cultural theories. We discuss the links between cultural dimensions derived from the field of intercultural communication and feedback behaviors and processes and provide propositions concerning culturally informed differences in specific feedback responses at individual and team levels.